Saturday

April 19, 2014

April 19, 2014

Posted by **Henry** on Tuesday, October 2, 2012 at 9:16pm.

- Math -
**Steve**, Wednesday, October 3, 2012 at 11:09amx^2 + bx + c = (x-r)^2

2r = -b

r^2 = c

b/c = r^2/(-r/2) = -2r

**Related Questions**

Quadratic -Make up a problem - I am supposed to write a quadratic equation in ...

Maths - Show proof of deriving the Quadratic Formula from the Quadratic Equation...

Maths - Show proof of deriving the Quadratic Formula from the Quadratic Equation...

math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...

maths - how do i find out the the equation of the line of symmetry for f(x)=ax^2...

math - Assume r and s are the roots of the quadratic equation ax^2 + bx + c = 0...

Math - Can someone please explain how to solve 3x^2+7x-15=0 by using the ...

Math - Quadratic - Rearrange this expression into quadratic form, ax2 bx c = 0...

Algebra - For what value(s) of b will x^2 + bx + 3 have exactly one root? I'm ...

math!HELP!! - write a quadratic equation in the variable x having the given ...